2017
DOI: 10.21273/jashs04030-17
|View full text |Cite
|
Sign up to set email alerts
|

MdMYB4, an R2R3-Type MYB Transcription Factor, Plays a Crucial Role in Cold and Salt Stress in Apple Calli

Abstract: MYB (v-myb avian myeloblastosis viral oncogene homologs) transcription factors (TFs) are involved in diverse physiological processes, including cell shape determination, cell differentiation, and secondary metabolism, as well as abiotic stress response. In the present study, MdMYB4, an R2R3-MYB protein that is a homolog of Arabidopsis thaliana MYB4, was identified and characterized. Quantitative real-time polymerase chain reaction (qRT-PCR) expression analysis demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…During freezing stress, low temperature induces the expression of MYB transcription factors and enhances anthocyanin synthesis to enhance freezing resistance. In addition, recent investigations in apple show that MdMYB4- transgenic apple calli exhibited enhanced tolerance to cold stress, as indicated by reduced electrolyte leakage value, and MDA content than the control calli [ 69 ]. The upregulation of MYB4 may increase cold resistance in wild apples.…”
Section: Discussionmentioning
confidence: 99%
“…During freezing stress, low temperature induces the expression of MYB transcription factors and enhances anthocyanin synthesis to enhance freezing resistance. In addition, recent investigations in apple show that MdMYB4- transgenic apple calli exhibited enhanced tolerance to cold stress, as indicated by reduced electrolyte leakage value, and MDA content than the control calli [ 69 ]. The upregulation of MYB4 may increase cold resistance in wild apples.…”
Section: Discussionmentioning
confidence: 99%
“…The fragments were then cloned into the pCambia super 1300 vector between Sal I and Kpn I restriction sites to generate B1, B2, and B3 constructs. The resulting recombinant vector was inserted into A. tumefaciens LBA4404 cells, which were then used to transform ‘Orin’ callus cells for 20 min, as described in Wu, Wang, Wu, Xu, and Han (). The cells were cocultured on agar‐solidified MS medium without antibiotics in darkness at 25°C for 24 hr then transferred to screening medium for 30 days to select for transformed cells.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that MeJA can activate antioxidant metabolic pathways and defense mechanisms in various crops and enhance cold tolerance [10]. In addition, some members of ERF, bHLH, MYB, DREB, and WRKY transcription factor families, such as ERF53 [11], ICE1, DREB1A [12], MYB4 [13], and WRKY19 [14], are also involved in regulating the expression of cold-stress response genes.…”
Section: Introductionmentioning
confidence: 99%